The Ratib Tulak Bala Tradition in Guguak Sungai Sariak, Padang Pariaman District - Nursaid, Nursaid; Rahman, Aida Fitri; Ningsih, Ayu Gustia (Universitas Negeri Semarang, 2023)
Ratib Rituals Tulak Bala ( refused bala ) have done by society Guguak in a manner down hereditary For prevent bad luck or disaster on life them . Objective from study qualitative This is For reveal history , practice , as well objective implemented ratib dead bala in the village guguak . With combine studies library and field, data for study This taken with use interview deep . Data analysis techniques were carried out with reduce , display , and withdraw conclusion from data. Ratib Ritual practice process dead reinforcements started from the mosque, after That next to road surround the village with read ratib custom . Procession this is at the end with read prayer together .